2005
DOI: 10.2166/wst.2005.0397
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of an Up-flow Anaerobic Sludge Bed (UASB) reactor at extreme salinity

Abstract: High salinity is one of the most well known inhibitors and salt concentrations above 1% are reported as highly saline. Salt may be found in the main collectors of municipal sewer systems which carry the risk of seawater infiltration and where domestic wastewaters are treated with landfill leachates such cases in Istanbul. Discharging of leachates into sewerage would also result in additional ammonium loads in Municipal Treatment Plants (MTPs). In this study, synthetic wastewater was fed to a lab-scale Upflow A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The fact that the COD removal efficiency was not affected by the increasing concentration of NaCl in the digester suggests the feasibility of POME treatment despite high level of NaCl recorded. This is consistent with the previous study on high removal efficiency in the high salinity environment on COD [7] and ammonia nitrogen [10] . In the case of anaerobic salt bacteria, Halanaaerobium lacusrosei better performance was observed [5] .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The fact that the COD removal efficiency was not affected by the increasing concentration of NaCl in the digester suggests the feasibility of POME treatment despite high level of NaCl recorded. This is consistent with the previous study on high removal efficiency in the high salinity environment on COD [7] and ammonia nitrogen [10] . In the case of anaerobic salt bacteria, Halanaaerobium lacusrosei better performance was observed [5] .…”
Section: Discussionsupporting
confidence: 94%
“…In a Specific Methanogenic Activity (SMA) study, researchers found that at 25°C, high NaCl content of 30 g L −1 and above, the bacteria could not be acclimatized even in 50 days which may be due to osmotic stress which inhibited the reaction pathways of the degradation process [9] . This is supported with another study which found the critical salinity level was 3% for the methanogens in the mesophilic anaerobic digesters [7] . On the contrary, in a modern Submerge Anaerobic Membrane Reactor (SAMBR), researchers found the biomass could rapidly acclimatize to salinity of up to 40 g L −1 with 40-60% of Dissolved Organic Carbon (DOC) removal and satisfactory methane production rate [11] .…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the literature, it is speculated that high concentration of salt formed during struvite precipitation may inhibit microbial activity in a following biological treatment process and cause decrease in the COD removal efficiency [18][19][20]. Following experiments were conducted for the investigation of effect of struvite pretreatment on the anaerobic treatment of leachate.…”
Section: Effect Of Struvite Precipitation On the Anaerobic Treatment mentioning
confidence: 99%
“…However, high salinity could cause osmotic stress on the bacterial cells and inhibition of reaction pathways in substrate degradation processes (Pollice et al 2000). High salinity was known to significantly reduce the treatment efficiency of anaerobic processes in mesophilic UASB reactors (Vallero et al 2004;Gomec et al 2005) and thermophilic UASB reactors (Vallero et al 2002). Vyrides et al highlighted the positive effect of the membrane in preventing the presence of high molecular weight organics in the effluent while also retaining biomass inside the reactor so that they could rapidly acclimatize to salinity (Vyrides and Stuckey 2009).…”
Section: Introductionmentioning
confidence: 99%